2018
DOI: 10.1002/ana.25208
|View full text |Cite
|
Sign up to set email alerts
|

De novo hotspot variants in CYFIP2 cause early‐onset epileptic encephalopathy

Abstract: Our findings suggest that de novo Arg87 variants in CYFIP2 have gain-of-function effects on the WAVE signaling pathway and are associated with severe neurological disorders. Ann Neurol 2018;83:794-806.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
89
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 45 publications
6
89
0
1
Order By: Relevance
“…Cyfip2 encodes cytoplasmic FMR1 interacting protein 2, which is involved in actin dynamics, axon elongation, and dendritic spine remodeling. Heterozygous de novo variants were identified in 4 unrelated individuals with epileptic encephalopathy . Functional studies showed gain‐of‐function effects resulting in dysregulation of actin dynamics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyfip2 encodes cytoplasmic FMR1 interacting protein 2, which is involved in actin dynamics, axon elongation, and dendritic spine remodeling. Heterozygous de novo variants were identified in 4 unrelated individuals with epileptic encephalopathy . Functional studies showed gain‐of‐function effects resulting in dysregulation of actin dynamics .…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous de novo variants were identified in 4 unrelated individuals with epileptic encephalopathy . Functional studies showed gain‐of‐function effects resulting in dysregulation of actin dynamics . C57BL/6NJ carries an S968F missense variant (rs240617401) in Cyfip2 that results in loss‐of‐function and was associated with altered cocaine‐response phenotypes in C57BL/6NJ vs C57BL/6J .…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent article published by Nakashima et al identifying de novo CYFIP2 Arg87 variants (p.Arg87Cys, p.Arg87Leu, and p.Arg87Pro) in individuals with early onset epileptic encephalopathy using whole‐exome sequencing. Soon after its publication, the p.Arg87Cys variant was also identified from independent whole‐exome or whole‐genome sequencing studies of individuals with West syndrome, and with intellectual disability and seizures, clearly demonstrating the association of CYFIP2 Arg87 variants with human neurological disorders.…”
mentioning
confidence: 97%
“…We thank Lee and colleagues for their interest in our recent article . They reported that the protein level of CYFIP2 mutants at Arg87 was lower than that of wild type (WT), suggesting their reduced stability.…”
mentioning
confidence: 99%
“…In our study, structural consideration suggested that Arg87 alterations disrupt hydrogen bonds between Arg87's side chain and the side chains of 2 glutamic acid residues of CYFIP2, in addition to disrupting a hydrogen bond between Arg87's side chain and the main chain of Tyr151 of WAVE, which is a highly conserved residue located in the meander regions of WAVE1 and is important for WRC activation. This leads to structural instability around the mutation site . Therefore, it is possible that Arg87 alterations induce structural instability of not only the WAVE regulatory complex but of CYFIP2 itself.…”
mentioning
confidence: 99%